2017
DOI: 10.1039/c7ra08041g
|View full text |Cite
|
Sign up to set email alerts
|

Chiisanoside, a triterpenoid saponin, exhibits anti-tumor activity by promoting apoptosis and inhibiting angiogenesis

Abstract: Chissanoside from Acanthopanax species exhibits anti-tumor activity by protecting liver function, regulating immunity, promoting apoptosis and inhibiting angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Chiisanoside was extracted from the leaf of A. sessiliflorus in our laboratory. The purity of CSS was determined by high‐performance liquid chromatography (HPLC) (purity > 98%) . Lipopolysaccharide (LPS, 99% purity) and d ‐galactosamine hydrochloride (d‐GalN, 98% purity) were produced by Sigma (St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiisanoside was extracted from the leaf of A. sessiliflorus in our laboratory. The purity of CSS was determined by high‐performance liquid chromatography (HPLC) (purity > 98%) . Lipopolysaccharide (LPS, 99% purity) and d ‐galactosamine hydrochloride (d‐GalN, 98% purity) were produced by Sigma (St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The purity of CSS was determined by high-performance liquid chromatography (HPLC) (purity > 98%). 21 Lipopolysaccharide (LPS, 99% purity) and D-galactosamine hydrochloride (d-GalN, 98% purity) were produced by Sigma (St Louis, MO, USA). The mice were randomly divided into four groups (n = 8): Control group, LPS/GalN group, LPS/GalN + CSS (30 mg kg −1 ) group, LPS/GalN + CSS (120 mg kg −1 ) group.…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…Although the antiangiogenic properties and VEGF inhibition by several tetracyclic triterpene saponins from ginseng, Rhizoma paridis , Acanthopanax sessiliflorus etc. have been reported, the knowledge about the effect of pentacyclic triterpene saponins on cancer angiogenesis is still limited [ 43 , 44 , 45 , 46 ]. In the present study, the wound healing assay showed that TSE1 almost totally inhibited OVCAR-3 cell migration at 2 μM after 24 h treatment ( Figure 4 a).…”
Section: Discussionmentioning
confidence: 99%
“…Lupane-type triterpenoids are distributed among many plant families. Previous studies have shown that several lupane triterpenes exhibit a wide range of pharmacological effects and engage in important biological activities, especially those involving anti-inflammation, liver protection, anti-tumor processes, and immune system regulation [26,27,28]. Based on our previous activity-guide isolation work, this work was undertaken to clarify the anti-inflammatory potential of HOA on LPS-stimulated RAW264.7 macrophages and its potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%